Add-on Therapy With Sacubitril/Valsartan and Clinical Outcomes in CRT-D Nonresponder Patients. Issue 4 (22nd April 2022) - Russo, Vincenzo; Ammendola, Ernesto; Gasperetti, Alessio; Bottino, Roberta; Schiavone, Marco; Masarone, Daniele; Pacileo, Giuseppe; Nigro, Gerardo; Golino, Paolo; Lip, Gregory Y. H.; D'Andrea, Antonello; Boriani, Giuseppe; et al.
Abstract: No data on the add-on sacubitril/valsartan (S/V) therapy among cardiac resynchronization therapy with a defibrillator (CRT-D) nonresponder patients are currently available in literature. We conducted a prospective observational study including 190 CRT-D nonresponder patients with symptomatic heart failure with reduced ejection fraction despite the optimal medical therapy from at least 1 year. The primary endpoint was the rate of additional responders (left ventricular end-systolic volume reduction >15%) at 12 months from the introduction of S/V therapy. At the end of the 12 months follow-up, 37 patients (19.5%) were deemed as "additional responders" to the combination use of CRT + S/V therapy. The only clinical predictor of additional response was a lower left ventricular ejection fraction [OR 0.881 (0.815–0.953), P = 0.002] at baseline. At 12 months follow-up, there were significant improvements in heart failure (HF) symptoms and functional status [New York Heart Association 2 (2–3) vs. 1 (1–2), P < 0.001; physical activity duration/day: 10 (8–12) vs. 13 (10–18) hours, P < 0.001]. Compared with the 12 months preceding S/V introduction, there were significant reductions in the rate of HF rehospitalization (35.5% vs. 19.5%, P < 0.001), in atrial tachycardia/atrial fibrillation burden [6.0 (5.0–8.0) % vs. 0 (0–2.0) %, P < 0.001] and in the proportions of patients experiencing ventricular arrhythmias (21.6% vs. 6.3%; P < 0.001). Our results indicate that S/V add-on therapy in CRT-D nonresponder patients is associated with 19.5% of additional responders, a reduction in HF symptoms and rehospitalizations, AF burden, and ventricular arrhythmias.